What is the relation and difference between `seqn` and `sequenceA`? - list

sequenceA :: Applicative f => [f a] -> f [a]
sequenceA [] = pure []
sequenceA (x:xs) = pure (:) <*> x <*> sequenceA xs
From Programming in Haskell by Hutton
seqn :: Monad m => [m a] -> m [a]
and is its implementation
seqn [] = return []
seqn (act:acts) = do x<- act
xs <- seqn acts
return (x:xs)
What is the relation and difference between seqn and sequenceA?
Since a monad is an applicative, is seqn the sequenceA limited to monad?

From the link at book (here) you added, the type of seqn is:
seqn :: Monad m -> [m a] -> m [a]
and it's implementation is:
seqn [] = return []
seqn (act:acts) = do
x <- act
xs <- seqn acts
return (x:xs)
And if you look at the type definition of sequenceA:
sequenceA :: (Traversable t, Applicative f) => t (f a) -> f (t a)
is more general, since Monad is an applicative, and your implementation:
sequenceA [] = pure []
sequenceA (x:xs) = pure (:) <*> x <*> sequenceA xs
is essentially the same as seqn
edit:
To answer the question in the comments
I asked a new question to see the differences between one and another. Hope it helps:
Proving equality of functions from Applicative and Monad
to summarize
There is no do notation for applicatives in Haskell, as you can read specifically in this segment.
This is a very nice article: Desugaring Haskell’s do-Notation into Applicative Operations, and its main idea is how to desugar the do notation of monads into applicatives if you want to know.
return and pure do exactly the same, but with different constraints, right?, so this part pure (:) and this part return (x:xs) you can see that are covered.
Then, here x <- act you are getting the value of act, and then the value of the recursion xs <- seqn acts , to finally wrap it with the return.
And that's what pure (:) <*> x <*> sequenceA xs is essentially doing.

Related

Modeling recursive fmap (sort of) over a list

I was wondering what the best way is to implement the following problem in a functional programming language (in this example Haskell):
You have a function (or a 'way') that turns 2 inputs, with the type a and b, in 2 ouputs of the same type (ex: Half adder). Lets call it f
in Haskell it would have this sort of type signature
a -> b -> (a, b)
And you have a list with elements of type a. (or another type of data structure).
Now if supplied with an initial b I want the following thing to happen (concept explained with recursive implementation):
Execute f with the initial b and the first element, modify the b and the element with the output of the function and repeat for the next element.
In Haskell:
exec _ [] _ = []
exec f (x:xs) b = let (x',b') = f x b in x':(exec f xs b')
What would be the best/most efficient way to model this sort of behavior.
It's mapM for the State monad.
OK, expanding a little.
Let's first enter this into ghci and see the type of the exec function:
Prelude> let {exec _ [] _ = []; exec f (x:xs) b = let (x',b') = f x b in x':(exec f xs b')}
Prelude> :t exec
exec :: (t2 -> t1 -> (t, t1)) -> [t2] -> t1 -> [t]
It's almost as you described, except that t and t2 don't have to be of the same type. That's good.
Now, another observation: we actually lose information, when we do what you describe. Specifically, we throw away the last value of b (or t, as ghci calls it). Let us preserve it for a moment; we can always throw it away later:
exec' _ [] b = ([], b)
exec' f (x:xs) b =
let (x',b') = f x b
(xs', b'') = exec' f xs b'
in (x':xs', b'')
And ghci says
Prelude> :t exec'
exec' :: (t2 -> t1 -> (t, t1)) -> [t2] -> t1 -> ([t], t1)
Than we can define
exec f xs b = fst $ exec' f xs b
But now the type of exec' contains a clear pattern. We can make it more explicit:
type S b c = b -> (c, b)
exec' :: (a -> S b c) -> [a] -> S b [c]
And now it's clear that S is almost exactly the State monad (well, it's actual definition in a modern setting is a bit more complicated, but not much: https://hackage.haskell.org/package/mtl-2.2.1/docs/Control-Monad-State-Lazy.html#t:StateT); really, it's just a newtype:
newtype State b c = State {runState :: b -> (c, b)}
And if we generalize the type of exec' to use an arbitrary monad instead of State, we get
Monad m => (a -> m c) -> [a] -> m [c]
Of course, we can't know for sure that such a thing actually exists, since we only have an implementation for the State monad, but... it does. It's called mapM (again, it's actual definition in the modern setting is more complicated: https://hackage.haskell.org/package/base-4.9.1.0/docs/Prelude.html#v:mapM) — which makes sense, since without a monad it would be just
(a -> c) -> [a] -> [c]
and that's exactly the type of map.
Of course, you can't be sure that exec' IS mapM without examining the latter's implementation. But in Haskell it just often happens that things that have the same type, if it's reasonably generic, are one and the same.
It also makes sense that State monad would be involved somehow — after all, you DO use b as a state, changing it as you go through the list.
So, if exec' is mapM, how do we get back to exec? Well, we need to go from the monadic value State b [c] to just [c], feeding it some b. We can — again — generalize; let's say, we go from State b d to d, without mentioning the list. And again — there is a function like that, it's called evalState: https://hackage.haskell.org/package/mtl-2.2.1/docs/Control-Monad-State-Lazy.html#v:evalState.
So, finally, we are able to produce the final result:
eval f xs b = evalState (mapM (\x -> state (\b -> f x b)) xs) b
which we can shorten to
eval f xs b = evalState (mapM (\x -> state (f x)) xs) b
or just
eval f xs = evalState (mapM (state . f) xs)
or even
eval f = evalState . mapM (state . f)
We can make it completely point-free, but that would be pointless (and contain too many points):
eval = (evalState .) . mapM . (state .)

You can find out if a list is a palindrome using (==) <*> reverse. How does it work?

I've tried to go through this using the types, but I'm still having difficulty understanding how it works.
Given:
> :t (==)
(==) :: Eq a => a -> a -> Bool
> :t (<*>)
(<*>) :: Applicative f => f (a -> b) -> f a -> f b
> :t reverse
reverse :: [a] -> [a]
> :t (==) <*> reverse
(==) <*> reverse :: Eq a => [a] -> Bool
Intuitively I can understand that it combines the equality operator with reverse in such a way that it creates a function that checks if a reversed list is equal to the original, but that's really not much more information than what is already pretty obvious.
Could someone break down in more detail the internals of what is actually happening here?
Start with the type of (<*>)
> : t (<*>)
(<*>) :: Applicative f => f (a -> b) -> f a -> f b
Now (->) k is an instance of Applicative, with implementation
instance Applicative ((->) k) where
pure a = \_ -> a
f <*> g = \k -> f k (g k)
In particular, the type of (<*>) specialised to (->) k is
(<*>) :: (k -> a -> b) -> (k -> a) -> (k -> b)
So the application (==) <*> reverse is
(==) <*> reverse = \k -> (==) k (reverse k)
= \k -> k == reverse k
i.e. it checks that a list is equal to its reverse.
Chris Taylor's answer is just right, but another way of looking at it, that I find more intuitive, is this: what the Applicative instance of function types does is this:
"Feed" the same argument value to two functions with the same argument type;
Combine their results with another function.
So basically, if you have f :: t -> a and g:: t -> b, the Applicative instance lets you map functions h :: a -> b -> c over the a and b results, under the assumption that f and g will be fed the same argument.
So think of how you'd write the palindrome test in a non-convoluted way:
palindrome :: Eq a => [a] -> Bool
palindrome xs = xs == reverse xs
xs appears twice on the right hand side of the definition: once as argument to ==, and a second time as argument to reverse. This automatically tells you that there is likely a way to use the (->) t applicative instance to eliminate the duplication. A different, perhaps more intuitive attack on this would be to first rewrite the function to this:
palindrome xs = id xs == reverse xs
...where id x = x is the identity function, which just returns its argument (and is a standard library function). Now you can rewrite that using the standard Applicative idiom (f <$> a0 <*> ... <*> an) to this:
-- Function that feed the same argument value to both `id` and `reverse`,
-- then tests their results with `==`:
palindrome = (==) <$> id <*> reverse
And now we can ask if there is a way to get rid of id in that rewrite. Since <$> is just shorthand for fmap, we can study the Functor instance for (->) t, which is just another way to express function composition:
instance Functor ((->) t) where
-- Mapping `f` over a *function* `g` is just the same as composing `f`
-- on the results of `g`.
fmap f g = f . g
One of the most important properties of function composition is that for any function f:
f . id = f
So applying that to the version of palindrome above, we get:
-- Since `f . id = f` for all `f`, then `(==) <$> id` is just `(==)`:
palindrome = (==) <*> reverse

Monad of list in Haskell

I'm trying to make this an instance of Monad in Haskell:
data Parser a = Done ([a], String) | Fail String
Now I try this code to make it an instance of Monad:
instance Functor Parser where
fmap = liftM
instance Applicative Parser where
pure = return
(<*>) = ap
instance Monad Parser where
return xs = Done ([], xs)
Done (xs, s) >>= f = Done (concat (map f xs)), s)
But this obviously doesn't work, because the function f in the bind-function is of the type a -> M b. So the (map f xs) function yields a list of M b-things. It should actually make a list of b's. How can I do this in Haskell?
NOTE: The actual error given by GHC 7.10.3 is:
SuperInterpreter.hs:71:27:
Couldn't match expected type `String' with actual type `a'
`a' is a rigid type variable bound by
the type signature for return :: a -> Parser a
at SuperInterpreter.hs:71:5
Relevant bindings include
xs :: a (bound at SuperInterpreter.hs:71:12)
return :: a -> Parser a (bound at SuperInterpreter.hs:71:5)
In the expression: xs
In the first argument of `Done', namely `([], xs)'
SuperInterpreter.hs:72:45:
Couldn't match type `Parser b' with `[b]'
Expected type: a -> [b]
Actual type: a -> Parser b
Relevant bindings include
f :: a -> Parser b (bound at SuperInterpreter.hs:72:22)
(>>=) :: Parser a -> (a -> Parser b) -> Parser b
(bound at SuperInterpreter.hs:72:5)
In the first argument of `map', namely `f'
In the first argument of `concat', namely `(map f xs)'
Failed, modules loaded: none.
leftaroundabout already showed you some of the problems.
Usually I expect a parser to be some kind of function that takes an input-String, maybe consuming some of this string and then returning an result together with the unconsumed input.
Based on this idea you can extent your code to do just this:
data ParserResult a
= Done (a, String)
| Fail String
deriving Show
data Parser a = Parser { run :: String -> ParserResult a }
instance Functor Parser where
fmap = liftM
instance Applicative Parser where
pure = return
(<*>) = ap
instance Monad Parser where
return a = Parser $ \ xs -> Done (a, xs)
p >>= f = Parser $ \ xs ->
case run p xs of
Done (a, xs') -> run (f a) xs'
Fail msg -> Fail msg
a simple example
here is a simple parser that would accept any character:
parseAnyChar :: Parser Char
parseAnyChar = Parser f
where f (c:xs) = Done (c, xs)
f "" = Fail "nothing to parse"
and this is how you would use it:
λ> run parseAnyChar "Hello"
Done ('H',"ello")
λ> run parseAnyChar ""
Fail "nothing to parse"
While it's not completely uncommon to define fmap = liftM and so on, this is a bit backwards IMO. If you first define the more fundamental instances and base the more involved ones on them, things often come out clearer. I'll leave <*> = ap, but transform everything else:
instance Functor Parser where -- Note that you can `derive` this automatically
fmap f (Done vs rest) = Done (map f vs) rest
fmap f (Fail err) = Fail err
instance Applicative Parser where
pure xs = Done ([], xs)
(<*>) = ap
Now with fmap already present, I can define Monad in the “more mathematical” way: define join instead of >>=.
instance Monad Parser where
return = pure
q >>= f = joinParser $ fmap f q
That means you'll work with intuitively handleable concrete values, rather than having to worry about threading a function through a parser. You can therefore see quite clearly what's going on, just write out the recursion:
joinParser :: Parser (Parser a) -> Parser a
joinParser (Fail err) = Fail err
joinParser (Done [] rest) = Done [] rest
joinParser (Done (Fail err : _) _) = Fail err
joinParser (Done (Done v0 rest0 : pss) rest) = ??
at this point you see clearly what Carsten already remarked: your Parser type doesn't really make sense as a parser. Both the inner and outer Done wrappers somehow have rest data; combining it would mean you combine the undone work... this is not what a parser does.
Search the web a bit, there's plenty of material on how to implement parsers in Haskell. In doubt, look how some established library does it, e.g. parsec.

All combinations of elements of two lists in Haskell

Given two lists, [a, b] and [c, d], I'd like to get the following result:
[(a,c), (a,d), (b,c), (b,d)]
How can I do this in Haskell? Is there a built-in function for this, or should I implement one myself?
[ (x,y) | x<-[a,b], y<-[c,d] ]
This doesn't really require any further explanation, does it?
Applicative style all the way!
λ> :m + Control.Applicative
λ> (,) <$> ['a','b'] <*> ['c','d']
[('a','c'),('a','d'),('b','c'),('b','d')]
(I've eschewed any String syntactic sugar above, in order to stay close to your example.)
For information, (,) is special syntax for a function that takes two arguments and makes a pair out of them:
λ> :t (,)
(,) :: a -> b -> (a, b)
Edit: As noted by leftaroundabout in his comment, you can also use liftA2:
λ> :m + Control.Applicative
λ> let combine = liftA2 (,)
λ> combine "ab" "cd"
[('a','c'),('a','d'),('b','c'),('b','d')]
How can you do this in an imperative pseudocode?
for each element x in [a,b]:
for each element y in [c,d]:
produce (x,y)
In Haskell, this is written as
outerProduct xs ys =
do
x <- xs -- for each x drawn from xs:
y <- ys -- for each y drawn from ys:
return (x,y) -- produce the (x,y) pair
(following comments by leftaroundabout) this is of course extremely close to how liftM2 monadic combinator is defined, so in fact
outerProduct = liftM2 (,)
which is the same as liftA2 (,), and its various re-writes in terms of list comprehensions, concatMap function, >>=, <$> and <*> operators.
Conceptually though this is the stuff of the Applicative – which would be better named as Pairing, – because this pairing up of the elements of two "containers" ⁄ "carriers" ⁄ whatever is exactly what Applicative Functor is about. It just so happens that Haskell's do notation works for monads, and not (yet) for applicatives.
In some sense compile-time nested loops are Applicative ⁄ Pairing functors; Monads add the ability to create nested loops on the fly, depending on the values produced by an "outer" enumeration.
The most inuitive would be using list comprehension, other aproaches include using applicative functors:
(,) <$> [1,2,3] <*> [4,5,6]
So what does this do?
Remember that (,) :: a -> b -> (a, b) Takes two arguments and returns a tuple.
<$> is acutally fmap, (<$>) :: Functor f => (a -> b) -> f a -> f b
It takes a function and lift it. In this case it takes (,) and lift it to work on list. So let x = (,) <$> [1,2] would generate x :: [b -> (Integer, b)] which is the the list of functions that takes b and returns tuple with one fixed argument (Integer,b). Finally we apply it using <*> to generate all the combinations.
use List Comprehension:
s = [a,b]
s' = [c,d]
all_combinations = [(x,y) | x <- s, y <- s']

What's wrong with my recursive list construction?

I've simplified the functions in question. I'm having trouble constructing a list inside a monad. I suspect a precedence problem.
newtype Boundary = MkBoundary Integer
testFunc :: [Boundary] -> [Maybe Integer]
testFunc (MkBoundary x:xs)
| (even x) = Just x : testFunc xs
| otherwise = Nothing : testFunc xs
testFunc _ = []
This works as expected. But I need to work in a monad. I'll use IO for this example
testFunc :: [Boundary] -> IO [Maybe Integer]
testFunc (MkBoundary x:xs)
| (even x) = return $ Just x : testFunc xs
| otherwise = return $ Nothing : testFunc xs
testFunc _ = []
No matter how I try to manipulate precedence, this breaks.
test.hs:6:35:
Couldn't match expected type `[Maybe Integer]'
with actual type `IO [Maybe Integer]'
In the return type of a call of `testFunc'
In the second argument of `(:)', namely `testFunc xs'
In the second argument of `($)', namely `Just x : testFunc xs'
Failed, modules loaded: none.
What I am trying to accomplish is a constructing a list, then returning it to IO. What am I doing wrong?
luqui answered your question, I will note a useful combinator.
If you want to perform a monadic action for all elements of a list, use "mapM". It is defined as:
mapM f [] = return []
mapM f (x:xs) = do y <- f x
ys <- mapM f xs
return (y:ys)
or something equivalent. [If you know some other combinators, you can write mapM with liftM2 and foldr.]
testFunc = mapM f
where f (MkBoundary x) | even x = do print x
return $ Just x
| otherwise = return Nothing
test in GHCi:
*Main> testFunc [MkBoundary 2, MkBoundary 3, MkBoundary 4]
2
4
[Just 2,Nothing,Just 4]
The problem is that testFunc xs returns an IO [Maybe Integer], and you are using it as the tail of a list as if it were a [Maybe Integer]. You need to extract:
| (even x) = do
xs' <- testFunc xs
-- now xs' is of type [Maybe Integer]
return $ Just x : xs'
Or, a more succinct way of saying the same thing:
| (even x) = (Just x :) <$> testFunc xs
((<$>) is from Control.Applicative and has type
(<$>) :: (a -> b) -> IO a -> IO b
specialized to IO . It applies a function to the value "inside" a monadic computation.)
Oh, also what missingno said :-)
You forgot to change the second case
test_func _ = return []
-- ^^^^^^
Also, I think your example function could be more clearly written as
test_func :: [Boundary] -> [Maybe Integer]
test_func = ...
monadic_test_func = [Boundary] -> IO [Maybe Integer]
monadic_test_func = return . test_func
This keeps the pure code separated from the nasty monad stuff. It also saves you from having to type "return" thrice! :)
And finally, why are you creating such a function in the first place? The monad part (at least in your example) seems to be somewhat unrelated to the main function logic (since you are just doing a return).
Perhaps you use some nice library functions to keep your function pure and untouched?
--instead of
monadic_value >>= monadic_test_func
--use
fmap test_func monadic_value
-- or equivalently
test_func <$> monadic_value
liftM test_func monadic_value